Awareness, access, and communication: provider perspectives on early intervention services for children with sickle cell disease - Heitzer, Andrew M.; MacArthur, Erin; Tamboli, Mollie; Wilson, Ashley; Hankins, Jane S.; Hoyt, Catherine R. (Frontiers in Pediatrics, 2024)
Purpose: This study aimed to identify determinants influencing the utilization of early intervention services among young children with sickle cell disease (SCD) based on perspectives from medical and early intervention providers. Design and Methods: Early intervention and medical providers from the catchment area surrounding St. Jude Children's Research Hospital and Washington University were recruited (20 total providers). Interviews were completed over the phone and audio recorded. All interviews were transcribed verbatim, coded, and analyzed using inductive thematic analysis. Results: Three overarching themes were identified from both groups: Awareness (e.g., lack of awareness about the EI system and SCD), Access (e.g., difficulties accessing services), and Communication (e.g., limited communication between medical and early intervention providers, and between providers and families). Although these three themes were shared by medical and early intervention providers, the differing perspectives of each produced subthemes unique to the two professional fields. Conclusions: Early intervention services can limit the neurodevelopmental deficits experienced by young children with SCD; however, most children with SCD do not receive these services. The perspectives of early intervention and medical providers highlight several potential solutions to increase early intervention utilization among young children with SCD.